Three-dimensional analysis of the dentoalveolar effects of slow and rapid maxillary expansion in bilateral complete cleft lip and palate: a randomized clinical trial - Alves, Arthur César de Medeiros (2015)
Introduction: The aim of this study was to compare the dentoalveolar effects of slow (SME) and rapid (RME) maxillary expansions in patients with bilateral complete cleft lip and palate. Methods: A total of fifty patients with bilateral complete cleft lip and palate diagnosed with maxillary dental arch constriction were randomly and equally divided into two groups. The SME group was comprised by patients who underwent slow maxillary expansion using quad helix appliance, and the RME group was composed by individuals who underwent rapid maxillary expansion using Hyrax expander. Digital dental models were acquired immediately pre-expansion (T1) and 6 months after the active expansion period (T2). Maxillary dental arch widths, arch perimeter, arch length, palatal depth and buccolingual inclination of posterior teeth were measured. Intergroup and inter-phase comparisons were performed with Students t test and paired t test, respectively (p<0.05). Results: Slow and rapid maxillary expansions caused significant and similar increase of arch widths and perimeter. Quad helix appliance showed a significant differential expansion greater in the intercanine width of maxillary dental arch compared to the intermolar width. Rapid maxillary expansion caused a significant decreasing of the arch length and palatal depth. Both appliances promoted similar significant proclination of maxillary canines. No differences were observed between the dentoalveolar effects of slow and rapid maxillary expansion. Conclusion: Slow and rapid maxillary expansions seem to cause similar dentoalveolar effects for the correction of maxillary dental arch constriction in patients with bilateral complete cleft lip and palate. Only quad helix appliance produced a differential expansion in the maxillary dental arch.